Oesophageal achalasia in an 11-year-old patient with persistent respiratory symptoms and suspected bronchial asthma - Julia Skulimowska; Agnieszka Strzelak; Agnieszka Szczukocka-Zych; Marek Krzysztof Kulus (Termedia Publishing House, 2023)
Oesophageal achalasia is a disease characterized by the inability of the lower oesophageal sphincter (LOS) to relax, which results in persistent contraction and the lack of peristaltic movement in the oesophageal body. It is a rare condition in children; therefore, its identification may be challenging. In this paper, we present a case of an 11-year-old patient with persistent cough and post-exercise tachypnoea, consulted due to uncontrolled asthma. After thorough diagnostic work-up, the patient was given the final diagnosis of oesophageal achalasia and was referred for surgical treatment. Uncontrolled asthma always requires the supervision of inhalation technique, consideration of treatment modification, and confirmation of the diagnosis. In this case, in-depth anamnesis and adequate interpretation of lung function tests allowed a correct diagnosis.